2010
DOI: 10.1016/j.neuroimage.2009.10.052
|View full text |Cite
|
Sign up to set email alerts
|

Shared neural resources between left and right interlimb coordination skills: The neural substrate of abstract motor representations

Abstract: Functional magnetic resonance imaging was used to reveal the shared neural resources between movements performed with effectors of the left versus right body side. Prior to scanning, subjects extensively practiced a complex coordination pattern involving cyclical motions of the ipsilateral hand and foot according to a 90 degrees out-of-phase coordination mode. Brain activity associated with this (nonpreferred) coordination pattern was contrasted with pre-existing isodirectional (preferred) coordination to extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 72 publications
4
34
0
Order By: Relevance
“…Effector-independent movement coding has been observed in the case of transfer learning experiments (Grafton, Hazeltine, & Ivry, 1998;Swinnen et al, 2010;van Mier & Petersen, 2006). Our results show that an effector-independent representation is likewise used in haptic perception.…”
Section: Discussionsupporting
confidence: 66%
“…Effector-independent movement coding has been observed in the case of transfer learning experiments (Grafton, Hazeltine, & Ivry, 1998;Swinnen et al, 2010;van Mier & Petersen, 2006). Our results show that an effector-independent representation is likewise used in haptic perception.…”
Section: Discussionsupporting
confidence: 66%
“…Swinnen and colleagues demonstrated that the left IFG/vPM and parietal regions are activated during both right and left hand-foot coordination movements. This suggests that the left parietal-premotor areas are candidates for effector-independent movement encoding as the highest level in the action representation hierarchy [43]. The overall conclusion gleaned from the above studies is that the left IFG/vPM plays an important role in both motor execution and imagery, irrespective of hand or foot side.…”
Section: Introductionmentioning
confidence: 84%
“…It may not matter that the kinesthetic signal arises from the "wrong" hand, because the haptic system may only be able to represent a single motion signal, regardless of its source. The mechanism for such simplification may arise from effector-independent representations of actions in the motor system, for which there is a large amount of neurophysiological evidence (49,50). An analogous case is known in vision, where the deflection of one eye is combined with retinal data from the other eye in spatial localization (51).…”
Section: Discussionmentioning
confidence: 99%